КОГЕНЕРАЦІЯ В МІКРОМЕРЕЖАХ - Кучерява, І.М. (Інститут електродинаміки Національної академії наук України, 2026)
This paper presents the current state in development of the most important technologies in the field of distributed generation, related to the processes of cogeneration and trigeneration. Cogeneration is a reliable, energy- and cost-effective and ecological solution in the combined production of electric and thermal energy. Trigeneration allows for the simultaneous production of electricity and heat with additional cold (cooling). The general characteristic of cogeneration systems, their advantages and negative factors are given. The different types of cogeneration systems (with the topping, bottoming and combined cycles of operation) are considered. The features of modern cogeneration plants and cogeneration control systems in microgrids are described and compared. The current state and importance of cogeneration in Ukraine are outlined. Ref. 26, figs. 5, tables 4.